Evaluation of vinasse as supplement in blood indicators in breeding sows - González, María C.; Rodríguez, Zoraya; Hernández, Lorena; Bocourt, R.; Yero, M. (Cuban Journal of Agricultural Science, 2020)
In order to determine the effects of vinasse as a supplement during the last third of gestation and lactation in blood indicators of breeding sows, an experiment was carried out under production conditions, in the Unidad Empresarial de Base Porcino No.1, Jesús Menéndez municipality, in Las Tunas province. The vinasse used came from the “Antonio Guiteras Holmes” distillery, located in Las Tunas. An amount of 48 hybrid sows (Yorkshire/Landrace) were used, which had between four and five parturitions. They were distributed according to a completely randomized design in four treatments (12 animals per group). Control sows consumed industrial feed and three treatments supplemented with 2.4 %, 3.4 % and 4.6 % of vinasse, respectively. Each sow constituted an experimental unit. Hemoglobin (Hb) and hematocrit (Hto) values of sows supplemented with vinasse were among the normal physiological parameters, with superior values that do not differ from each other, except in the 2.4% treatment, in which they did not differ from the control (P <0.0001). In the final evaluation, the inclusion of 4.6% of vinasse showed the best results for both indicators (P<0.001), with values of 12.82g L-1 and 39.29 %, respectively. Leukocytes, neutrophils and lymphocytes proportionally increased to the level of the vinasse used. Total serum proteins increased with respect to control, regardless of vinasse level. It is concluded that the inclusion of up to 4.6 % of vinasse, as a supplement in the diet of breeding sows, during the last third of gestation and lactation, improves blood indicators and favors those associated with immunological activity. Keywords: sows, vinasse, hematology